Le caroubier : Valorisation et utilisation industrielle - BOUHREM, Ilyes (My University, 2019)
this investigation was performed in order to valorize the carob by two different points of view, the first one is by gaining knowledge on the rheological behavior of wheat flour enriched with different amounts of carob flour (5%,10% and 15%).the second one, is by measuring and analyzing the antioxidant power of carob powder over a sheep meat(Gigot) with different concentrations (5%,10% and 15%). It was approved through this study that the carob powder has an effective antioxidant power with a concentration of 15%. in the other hand the substitution of wheat flour with a concentration of 1% of carob powder doesn’t affect the rheological behaviors of the flour. Indeed, it optimize the (P/L) and work flour parameters (W).
Keywords: Carob; Wheat Flour; Meat; Rheological; Antioxidant